Análisis técnico de la seguridad en los sistemas informáticos de la Unidad Educativa Eneida Uquillas De Rojas. - Castillo León, Edder Santiago (2022)
The present research work corresponds to the subject of Technical Analysis of security in computer systems, a study that had as its place of origin the Educational Unit "Eneida Uquillas de Rojas", it was founded in 1946, and is located in the La Teresa campus, in the Febres Cordero Parish, where some 200 students reside, the purpose of the research is to carry out a technical analysis in the computer system of the Educational Unit, to improve the security of its information systems, for which 12 teachers who collaborated served as a sample in the study, where a descriptive level investigation was used, this is the first level in taxonomy of scientific research, where it allows collecting, analyzing, and being able to establish a relationship according to the theme, for the process of this investigation used field research that through direct observation allows to show if there are vulnerabilities in computer systems in an agile and precise way, in which it is expected to find old units, unsupported operating systems, routers or wiring systems in poor condition, etc. A small survey was also carried out that concluded that, in the unit, evidence was found that the Windows that the institution has is Windows 7, an operating system that is no longer supported and is a drain speaking in computer terms, for what this represents a great vulnerability at present.